Generalizability of demographically corrected Zambian neuropsychological norms to South African women. (10th December 2019) - Denckla, Christy A.; Spies, Georgina; Heaton, Robert; Vasterling, Jennifer; Franklin, Donald; Korte, Kristina J.; Colgan, Courtney; Henderson, David C.; Koenen, Karestan C.; Seedat, Soraya
Abstract: Objective: Demographically corrected norms typically account for the effects of age, education, and in some cases, sex and other factors (e.g. race/ethnicity). However, generalizability of normative standards to different countries and ethnic groups is not universal. This study sought to determine whether demographically specific Zambian neuropsychological norms would generalize to a group of South African women. Method: 212 English-Xhosa bilingual, South African (SA) women were administered a comprehensive neuropsychological (NP) test battery in either English or Xhosa. We examined rates of "impairment" using Global Deficit Scores (GDS) based upon published, demographically corrected norms from a nearby African country (Zambia). Using multiple regression, we examined the extent to which Zambian norms "corrected" for the effects of age and education in this SA sample. Results: Compared to the normative standards from Zambia, the South African women performed somewhat worse than expected on a few test measures and better than expected on others, but their GDS and associated "impairment" rates were close to what was seen in Zambia. Demographically corrected Zambian norms adequately adjusted for the effects of age and years of education in this sample of SA women, with the exception that Zambian norms appeared to "under correct" for the positive effects of years of education on tests of information processing speed. Conclusions: Demographically corrected norms developed for Zambia may adequately adjust for the effects of age in SA women. Further research is needed to determine whether additional corrections for education are needed in SA, especially for tests of information processing speed.